Komposisi Visual dan Tata Cahaya Pada Film Netflix Berjudul Squid Game - Stephani Inesia Linando; Martinus Eko Prasetyo; Winnie Winnie (Jurnal Bahasa Rupa, 2022)
2021 was the year of Netflix’s sensation, the South Korean drama series, "Squid Game" directed by Hwang Dong Hyuk. The visual and audio production are extraordinary, and the idea of ​​the storyline is quite interesting, resulted in one of the highest ratings in Netflix. This analysis examines the creative process in the idea of ​​pictures taken in the series by studying cinematographic visual composition based on composition theory by Paul Wheeler. In this paper, the authors try to examine some of the best scenes as a sampling study, and how a composition can provide an important role in communicating the drama series’ storyline. Surely this can be developed as a further learning medium in the study of cinematography and composition.